Krepitev moči kot temeljno orodje socialnega dela - Videmšek, Petra (Socialno delo, 2008)
Aiming towards the distribution of power among participants in a process, the concept of empowerment represent the guiding force of social work profession. The development of the concept within the profession since the 1970s and the difference between the inital attempts and the ways the concept is used today are presented. The division of the concept into collective and individual levels seems to be the main characteristics of this development. Examples are given of collective and individual empowerment from the author's co-operation with focus groups. Summarising referential literature, the author finds that authors are far from agreeing on what empowerment is and when the concept really began to be used, and she stresses that the concept should rather be defined by those for whom it is designed - people with experience. To illustrate her ptoposal, the author presents definitions of concept given by people with experience who participated in the focus group.
Keywords: krepitev moči; social work; socialno delo; podpora; pomoč; terminologija; terminology